Histomorphometric study of role of lactoferrin in atrophy of the intestinal mucosa of rats - Caruso, Marcio; Demonte, Aureluce [UNESP]; Neves, Valdir Augusto [UNESP] (Scientific Research Publishing, 2012)
The purpose of this work was to study the effects of oral administration of lactoferrin (Lf) in rats subjected to atrophy of the small intestine induced by a diet based on soy protein concentrate as the main protein source. We used 24 male Wistar rats aged 40 days, kept in individual cages under appropriate conditions of temperature, light and humidity. The animals were divided into four groups (n = 6); 1) group SL received soy-based food and, once a day, a supplement of 200mg/kg of Lf administered by gavage; 2) group Si received the soy feed without supplement of Lf; 3) group CL received a diet based on casein plus Lf; 4) group Ci received the casein diet without supplement of Lf. At the end of fifteen days, a 10 mm segment of the initial portion of the small intestine was sectioned and subjected to morphometry of the intestinal crypts and villi and assessment of the number and size of myofibroblasts. Comparison between groups showed that the length of the villi was similar in groups Ci and CL and higher in CL than in SL; SL than in Si, in Ci than in SL, and in Ci than in Si to Ci. The crypt depth was similar in SL and CL, SL and Ci and Ci and CL and was higher in Si than in Ci and in Si than in SL. The number of myofibroblasts was higher in SL than in CL, in SL than in Si, in CL than in Ci, and in SL than in and Ci; between Ci and Si there was no difference. The area of myofibroblasts was similar between the groups SL and CL and Si and Ci and higher in SL than in Si, and in Cl than in and Ci, and in SL than in Ci. All statistical analysis assumed significance when p < 0.05. From these results, we conclude that lactoferrin increases the number and size of the pericrypt myofibroblasts and stimulates rapidly the regeneration of atrophied villi.
Keywords: Intestinal Villi; Lactoferrin; Myofibroblast; Atrophy